The effect of electoral politics on the distribution of public spending in the context of democratic transition: evidence from Tunisia - Kaddour Mehiriz (3129189) (2025)
Redistributive politics theories suggest that in democracies, political parties use redistribution to gain the support of their core constituencies. This study examines this assumption in the context of the democratic transition in Tunisia. Using data on legislative elections and public expenditures for the period 2011–2019 and panel fixed effect methods, we found a negative association between government parties’ share of seats and public spending per capita, rejecting therefore the core constituencies assumption. Moreover, this negative relationship was observed in the case of Ennahda party that, after losing the 2014 elections, entered a coalition government led by Nidaa Tounes, but not in the latter's case. These results suggest that this pattern of spending distribution is part of a general strategy according to which, instead of prioritizing short term electoral benefits, the ruling parties, particularly Ennahda, strived to build strong political support for democratic transition and avert autocratic reversal threats. However, the electoral cost of this strategy is mainly borne by the coalition members that are more likely to suffer from the adverse effects of the reestablishment of autocracy. This study thus underlines the importance of considering the fragility of democratic institutions and implications of their eventual collapse in studying redistributive politics. Other Information Published in: Democratization License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13510347.2025.2576488